2017
DOI: 10.1007/s10620-017-4516-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of Helicobacter pylori with Chronic Kidney Diseases: A Meta-Analysis

Abstract: The estimated prevalence of H. pylori in patients with non-dialysis-dependent kidney diseases is 53%. This study does not support the association between H. pylori infection and non-dialysis-dependent kidney diseases nor CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The pooled risk RR of ESRD in patients with H. pylori was 0.61 (0.03‐12.20), but these data were limited to only two cohort studies with contradictory results and different selection criteria. The meta‐analysis of nine eligible cross‐sectional studies conducted by Wijarnpreecha et al . did not support the association between H. pylori infection and nondialysis‐dependent kidney diseases (OR: 1.20, 0.73‐1.97) nor chronic kidney diseases (OR: 1.00, 0.58‐1.71).…”
Section: Miscellaneousmentioning
confidence: 87%
“…The pooled risk RR of ESRD in patients with H. pylori was 0.61 (0.03‐12.20), but these data were limited to only two cohort studies with contradictory results and different selection criteria. The meta‐analysis of nine eligible cross‐sectional studies conducted by Wijarnpreecha et al . did not support the association between H. pylori infection and nondialysis‐dependent kidney diseases (OR: 1.20, 0.73‐1.97) nor chronic kidney diseases (OR: 1.00, 0.58‐1.71).…”
Section: Miscellaneousmentioning
confidence: 87%
“…In summary, re-analysis of the data reported by Wijarnpreecha et al [1] using alternate and arguably superior statistical methods would reveal a significant correlation between CKD and Hp prevalence.…”
mentioning
confidence: 89%
“…The Wijarnpreecha et al [1] study, entitled ''Association of Helicobacter pylori with Chronic Kidney Diseases: A Meta-Analysis,'' published in Digestive Diseases and Sciences, investigated the relationship between H. pylori infection and the incidence of chronic kidney disease (CKD) and non-dialysis-dependent kidney disease. Wijarnpreecha et al reported that the association in question was not significant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another meta‐analysis by the same authors included nine cross‐sectional studies and estimated a pooled OR of 1.20 (95% CI: 0.73, 1.97) for H. pylori positivity in patients with non‐dialysis‐dependent kidney disease when compared to controls. The meta‐analysis was then limited to studies evaluating the risk of H. pylori in chronic kidney disease (CKD) and showed a pooled OR of 1.00 (95% CI: 0.58, 1.71), not significant for the association …”
Section: Kidney Diseasesmentioning
confidence: 99%